Involving Yourself in Halal Life: Surah Al-Baqarah Verse 168 Perspective on Halal Labeled Food - Harahap, Indah Salsabila (Yayasan Salam Cerdas Al-Fattah, 2023)
This research details the relationship between food labeled halal and Surah Al-Baqarah Verse 168 in the context of the daily lives of Muslims, especially regarding the phenomenon of globalization and the development of Muslim consumer needs. Factors such as awareness, education, product availability and increasing income were identified as key drivers in selecting halal food products. In the context of halal restaurants, the Toyyiban Halalan concept encourages not only food that is recognized by Islam but also quality, cleanliness and production safety. However, in Indonesia, research highlights challenges related to the misuse of halal certificates with several obstacles such as high costs, complex management, and lack of socialization from the MUI. The research method used is descriptive qualitative, with literature analysis showing that halal certification provides a guarantee of safety for Muslim consumers. Surah Al-Baqarah Verse 168 emphasizes the obligation to consume halal food and thayyib, emphasizing cleanliness as a key aspect. This verse also warns against the bad influence of Satan and encourages you to choose food in an orderly manner. In business, the practice of halal labels creates positive relationships between Muslim producers and consumers. From a spiritual perspective, choosing food according to the principles of this verse creates awareness of the cleanliness and halalness of food. Research recommendations emphasize increasing consumer and producer understanding of halal principles and Islamic business ethics through better education and awareness. Overall, this research contributes to an in-depth understanding of the positive impact of the association of halal-labeled food with Surah Al-Baqarah Verse 168 on the spiritual, health and business aspects of Muslims. Through recommendations, this research aims to promote a halal lifestyle in accordance with Islamic values through increasing awareness and education. Keywords: Halal, Halal Certification, Halal Restaurants, Surah Al-Baqarah Verse 168, Consumer Trust